Data curation issues in transitioning a field science collection of long-term research data and artefacts from a local repository to an institutional repository - Kaplan, Nicole E., author; Draper, Daniel C., author; Bastian, Dawn E. (Dawn Elaine), 1961-, author; Moore, John C., author; Baker, Karen S., author; Swauger, Shea, author; SGS-LTER, Colorado State University, publisher (Colorado State University. Libraries, 2014)
Transition a local 32 year project, the Shortgrass Steppe Long-Term Ecological Research (SGS-LTER), with over 100 data packages and related digital artefacts, to an Institutional Repository (IR) at Colorado State University (CSU) Libraries to ensure persistent, reliable, and interoperable access to our collection of scientific data. Our collaborative team envisions being part of a larger information environment, which enables sharing of knowledge and data - a web of repositories. Poster presented at the 9th International Digital Curation Conference held in San Francisco, California on February 25, 2014. Refereed.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: Central Plains Experimental Range; shortgrass steppe; long term ecological research; grassland ecology; data; artefacts; information infrastructure; access; collaborative team; Pawnee National Grassland